2016
DOI: 10.1111/jfd.12541
|View full text |Cite
|
Sign up to set email alerts
|

Viral encephalopathy and retinopathy in aquaculture: a review

Abstract: Viral encephalopathy and retinopathy (VER), otherwise known as viral nervous necrosis (VNN), is a major devastating threat for aquatic animals. Betanodaviruses have been isolated in at least 70 aquatic animal species in marine and in freshwater environments throughout the world, with the notable exception of South America. In this review, the main features of betanodavirus, including its diversity, its distribution and its transmission modes in fish, are firstly presented. Then, the existing diagnosis and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
128
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 182 publications
(418 reference statements)
1
128
0
Order By: Relevance
“…Although we could not get and use SJNNV and TPNNV genotype as positive controls in this study, the developed two‐step RT‐PCR methods might be sufficient to detect and discriminate the SJNNV and TPNNV in samples, because all used primers were developed by high nucleotide sequence identity to each corresponding region of genotypes (Figure ). Additionally, it has been reported that TPNNV, known to infect only tiger puffer Takifugu rubripes (Temminck & Schlegel), was detected exclusively in Japan and has never been reported so far since its first isolation in 1993 (Doan, Vandeputte, Chatain, Morin, & Allal, ; Nishizawa et al., ). Also, although epidemics of SJNNV has been reported only in Japan among Asian countries (Doan et al., ), even in Japan, except only one case of SJNNV monitored in about 700 wild finfish by two‐step RT‐PCR (Sakamoto et al., ), all remaining nodaviruses in finfish and squid samples were identified recently as RGNNV type (Gomez, Mori, Okinaka, Nakai, & Park, ; Gomez et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we could not get and use SJNNV and TPNNV genotype as positive controls in this study, the developed two‐step RT‐PCR methods might be sufficient to detect and discriminate the SJNNV and TPNNV in samples, because all used primers were developed by high nucleotide sequence identity to each corresponding region of genotypes (Figure ). Additionally, it has been reported that TPNNV, known to infect only tiger puffer Takifugu rubripes (Temminck & Schlegel), was detected exclusively in Japan and has never been reported so far since its first isolation in 1993 (Doan, Vandeputte, Chatain, Morin, & Allal, ; Nishizawa et al., ). Also, although epidemics of SJNNV has been reported only in Japan among Asian countries (Doan et al., ), even in Japan, except only one case of SJNNV monitored in about 700 wild finfish by two‐step RT‐PCR (Sakamoto et al., ), all remaining nodaviruses in finfish and squid samples were identified recently as RGNNV type (Gomez, Mori, Okinaka, Nakai, & Park, ; Gomez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that TPNNV, known to infect only tiger puffer Takifugu rubripes (Temminck & Schlegel), was detected exclusively in Japan and has never been reported so far since its first isolation in 1993 (Doan, Vandeputte, Chatain, Morin, & Allal, ; Nishizawa et al., ). Also, although epidemics of SJNNV has been reported only in Japan among Asian countries (Doan et al., ), even in Japan, except only one case of SJNNV monitored in about 700 wild finfish by two‐step RT‐PCR (Sakamoto et al., ), all remaining nodaviruses in finfish and squid samples were identified recently as RGNNV type (Gomez, Mori, Okinaka, Nakai, & Park, ; Gomez et al., ). Therefore, the prevalence of shellfish with SJNNV and TPNNV was not likely to be sufficient to be monitored even in Japan, although further study is required to confirm DMT‐2 RT‐PCR sensitivity for SJNNV and TPNNV.…”
Section: Discussionmentioning
confidence: 99%
“…Viral nervous necrosis (VNN), also known as viral encephalopathy and retinopathy (VER), is an important cause of marine fish disease worldwide. It is frequently fatal and accounts for severe economic losses in the aquaculture industry, particularly in larval and juvenile stages (Doan, Vandeputte, Chatain, Morin, & Allal, ). The causative agent, nervous necrosis virus (NNV), genus Betanodavirus (Thiéry et al., ), can infect a wide range of marine farmed and wild fish species (Doan et al., ) and has also been isolated from freshwater fish (Shetty, Maiti, Shivakumar Santhosh, Venugopal, & Karunasagar, ) and invertebrates (Gomez et al., ; Volpe et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently fatal and accounts for severe economic losses in the aquaculture industry, particularly in larval and juvenile stages (Doan, Vandeputte, Chatain, Morin, & Allal, ). The causative agent, nervous necrosis virus (NNV), genus Betanodavirus (Thiéry et al., ), can infect a wide range of marine farmed and wild fish species (Doan et al., ) and has also been isolated from freshwater fish (Shetty, Maiti, Shivakumar Santhosh, Venugopal, & Karunasagar, ) and invertebrates (Gomez et al., ; Volpe et al., ). The affected fish commonly display lesions in the central nervous system, with vacuolization and necrosis observed in brain, retina and spinal cord, leading to a range of neurological signs such as abnormal swimming behaviour, anorexia and changes in coloration (Doan et al., ; Maltese & Bovo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Viral encephalopathy and retinopathy (VER), otherwise known as viral nervous necrosis (VNN), is a highly infective neuropathological condition that affects a wide range of fish species worldwide and causes mass mortalities, mainly in larval and juvenile stages [1]. The causative agents are Nervous necrosis viruses (NNV), small and non-enveloped viruses belonging to the G. Betanodavirus , F. Nodaviridae .…”
Section: Introductionmentioning
confidence: 99%